Short Interest and Lottery Stocks. Issue 1 (25th April 2018) - Bergsma, Kelley; Tayal, Jitendra
Abstract: We find short interest‐related mispricing is strongest in lottery stocks. As stocks become more lottery‐like, arbitrage risk increases, resulting in higher overpricing (underpricing) in high (low) relative short interest (RSI) stocks. Monthly portfolio alphas are –1.61% for high RSI lottery stocks, whereas high RSI stocks with the least lottery‐like attributes show statistically insignificant alphas. Among lightly shorted stocks, lottery securities exhibit monthly alphas of 1.80%. Thus, although lottery stocks as a group typically underperform, investors can earn positive abnormal returns in lightly shorted lottery stocks. Our results suggest that lottery stocks' greater noise trader risk and higher transactions costs impedes arbitrage in short interest‐related mispricing.